Fotobiomodulação na cicatrização de ferida por picada de aranha: relato de caso - Gonçalves, Natalia; Scotergagna Leal, Matheus (Revista Feridas, 2023)
To report a nurse’s experience in caring for a woman injured by a spider bite. Method: experience report guided by Wanda Horta’s conceptual model. Results: The patient presented with a spider bite injury on the right foot, with moderate stabbing pain, superficial wound, edema and hyperemic halo. Treatment was started with low power laser, 2 J red, until complete healing, which occurred in seven days. From the nurse’s perspective, the systematization of care through the nursing process facilitated the conduction of the work and the use of the laser, improved the prognosis and favored the healing of the lesion. Conclusion: the systematization of nursing care empowers and qualifies the work of nurses And the use of new technologies for the treatment of wounds improves people’s quality of life as it facilitates and speeds up the wound healing process.